Enhancement of reproductive performance in postpartum Murrah buffaloes treated with prostaglandin and gonadotrophin releasing hormone - RK Malik,; Pardeep Singh,; IS Lohan,; RK Tuli, (Journal of Livestock Biodiversity, 2025)
Fifty postpartum buffaloes were divided into five groups, treatments (T1, T2, T3, T4) and one control (T5). Prostaglandin (Lutalyse) and gonadotrophin releasing hormone (receptal) were used in combination or alone to induce cyclicity. All the animals were palpated per rectum manually, on days 10, 15, 27, 35, 45, 50 and 60 postpartum to note reproductive status. Treatments (T1, T2, and T3) differed significantly (P